2017
DOI: 10.29267/mxjb.2017.2.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Biomasa de Tenebrio molitor como inductor de lipasas y proteasas producidas por Paecilomyces fumosoroseus

Abstract: Los hongos entomopatógenos son microorganismos comúnmente usados en prácticas de biocontrol de nematodos, insectos, entre otros. El principal mecanismo de acción de estos hongos es el parasitismo mediado por enzimas líticas, las cuales dependen de la interacción directa del microorganismo con sustratos inductores. En el presente estudio se evaluó la influencia de 8 generaciones continuas del hongo Paecilomyces fumosoroseus y el efecto de la adición de biomasa de Tenebrio molitor en el medio de cultivo para la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…On the other hand, Khan et al [ 87 ] reported that lipases, proteases and chitinases have the strongest entomopathogenic effect. Thus, the production of these enzymes by P. fumosoroseus has been effective in the control of Tenebrio molitor [ 88 ], Trialeurodes vaporariorum [ 89 ] and Plutella xylostella [ 90 ]. P. farinosus (Holmsk.)…”
Section: Biological Control Mechanisms Of the Genus Paecmentioning
confidence: 99%
“…On the other hand, Khan et al [ 87 ] reported that lipases, proteases and chitinases have the strongest entomopathogenic effect. Thus, the production of these enzymes by P. fumosoroseus has been effective in the control of Tenebrio molitor [ 88 ], Trialeurodes vaporariorum [ 89 ] and Plutella xylostella [ 90 ]. P. farinosus (Holmsk.)…”
Section: Biological Control Mechanisms Of the Genus Paecmentioning
confidence: 99%
“…Lipases, proteases and chitinases are the most effective entomopathogenic enzymes (Khan et al, 2004). Thus, it has been demonstrated that the synthesis of these enzymes by P. fumosoroseus is effective against Tenebrio molitor (Gómez et al, 2017), Trialeurodes vaporariorum (Castellanos-Moguel et al, 2007 and other infections. Numerous studies on Paecilomyces' nematicidal effect have been conducted.…”
Section: Biological Control Of Pests In Major Tropical Vegetable Crop...mentioning
confidence: 99%